2004
DOI: 10.1179/136217104225017053
|View full text |Cite
|
Sign up to set email alerts
|

Welding problems with thin brass plates and tungsten inert gas pulse welding

Abstract: Brass materials are widely used as engineering materials in industry because of their high strength, high corrosion resistance, and high electrical and thermal conductivity. They are easily shaped and they possess a pleasant appearance. However, it is difficult to weld brasses. The main problem with these alloys in fusion welding is the evaporation of zinc during the welding process. After welding, the weld metal becomes porous. Moreover, since the amount of zinc in the alloy is reduced due to evaporation, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 4 publications
0
15
0
1
Order By: Relevance
“…The thickness of the brass material used in the experiments was 1 mm. The data, related to welding current, welding velocity and arc length are taken from these experimental results [8].…”
Section: Application Of the Gawcem/gawvem Model And Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The thickness of the brass material used in the experiments was 1 mm. The data, related to welding current, welding velocity and arc length are taken from these experimental results [8].…”
Section: Application Of the Gawcem/gawvem Model And Resultsmentioning
confidence: 99%
“…The study conducted by Meran et al [8] has indicated that the selection of an unsuitable welding current and welding speed leads to some holes, zinc oxide and the excess penetration. The welding bead of the desired quality was not formed [8]. Evaporation takes place, pores appear in the welding bead, zinc oxide precipitates on the surface of welding bead and the brass loses its yellowish color and takes a reddish color.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations